Neuromuscular Electrical Stimulation Use after Total Knee Arthroplasty Improves Early Return to Function: A Randomized Trial - Klika, Alison K.; Yakubek, George; Piuzzi, Nicholas; Calabrese, Gary; Barsoum, Wael K.; Higuera, Carlos A. (The Journal of Knee Surgery, 2020)
Neuromuscular electrical stimulation (NMES) has been reported as an effective method for quadriceps strengthening which could attenuate muscle loss in the early total knee arthroplasty (TKA) postoperative recovery period. The purpose of this randomized controlled trial was to test whether postoperative use of NMES on TKA patients results in increased quadriceps strength and ultimately improved functional outcomes. This randomized controlled clinical trial of 66 primary TKA patients was conducted at a large academic medical center. Patients were randomized 2:1 into treatment (NMES use, n = 44) or control arm (no NMES, n = 22). Patients who used the device for an average of 200 minutes/week or more (starting 1 week postoperative and continuing through week 12) were considered compliant. Baseline measurements and outcomes were recorded at 3, 6, and 12 weeks postoperatively, and included quadriceps strength, range of motion (ROM), resting pain, functional timed up and go (TUG), stair climb test, and knee injury and osteoarthritis outcome score (KOOS) and veterans rand 12-item health survey (VR-12) scores. Patients in the treatment arm (NMES use) experienced quadriceps strength gains over baseline at 3, 6, and 12 weeks following surgery, which were statistically significant compared with controls with quadriceps strength losses at 3 (p = 0.050) and 6 weeks (p = 0.015). The TUG improvements for patients treated with NMES showed significant improvements at 6 (p = 0.018) and 12 weeks (p = 0.003) postoperatively. Use of a home-based application-controlled NMES therapy system added to standard of care treatment showed statistically significant improvements in quadriceps strength and TUG following TKA, supporting a quicker return to function.
Keywords: total knee arthroplasty; function; recovery; neuromuscular electrical stimulation therapy